2010
DOI: 10.1007/s10709-010-9460-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal mapping of the major and minor ribosomal genes, (GATA)n and U2 snRNA gene by double-colour FISH in species of the Batrachoididae family

Abstract: In the present study dual-colour fluorescence in situ hybridization (FISH) was performed to study the chromosomal distribution of 18S and 5S rDNAs, (GATA)(n) and 5S rDNA, and U2 snRNA and 18S rDNA in four species of Batrachoididae family: Amphichthys cryptocentrus, Batrachoides manglae, Porichthys plectrodon and Thalassophryne maculosa. The 18S rDNA signals were present in only one pair of chromosomes in all the four Batrachoididae species. The 5S rDNA was mapped on one pair of chromosomes, except in B. mangla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
48
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 42 publications
10
48
0
2
Order By: Relevance
“…For example, from the 5 existing subtypes of U snRNA genes, U1 snDNA was mapped only in cichlid species, and its position was highly conserved, with a single pair of U1 snDNA-bearing chromosomes for all analyzed species [Cabral-de-Mello et al, 2012]. Conversely, U2 snDNA cluster location was reported in 5 Batrachoididae, 2 Moronidae, 1 Bagridae, and 1 Haemulidae species [Merlo et al, , 2012aÚbeda-Manzanaro et al, 2010;Supiwong et al, 2013] and evidenced a more diversified scenario, particularly in the Batrachoididae family with species presenting (i) compartmentalization of this sequence in a single pair, (ii) a very widely scattered distribution throughout all chromosomes, or (iii) simultaneous scattered and compartmentalized organization [Úbeda-Manzanaro et al, 2010]. Here, we show that the U2 snDNA is compartmentalized and the number of U2 snDNAbearing chromosomes is conserved in Gymnotus .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, from the 5 existing subtypes of U snRNA genes, U1 snDNA was mapped only in cichlid species, and its position was highly conserved, with a single pair of U1 snDNA-bearing chromosomes for all analyzed species [Cabral-de-Mello et al, 2012]. Conversely, U2 snDNA cluster location was reported in 5 Batrachoididae, 2 Moronidae, 1 Bagridae, and 1 Haemulidae species [Merlo et al, , 2012aÚbeda-Manzanaro et al, 2010;Supiwong et al, 2013] and evidenced a more diversified scenario, particularly in the Batrachoididae family with species presenting (i) compartmentalization of this sequence in a single pair, (ii) a very widely scattered distribution throughout all chromosomes, or (iii) simultaneous scattered and compartmentalized organization [Úbeda-Manzanaro et al, 2010]. Here, we show that the U2 snDNA is compartmentalized and the number of U2 snDNAbearing chromosomes is conserved in Gymnotus .…”
Section: Resultsmentioning
confidence: 99%
“…cluding transposable elements, histone genes, microsatellite repeats and/or U1/U2 small nuclear RNA (snRNA) genes [Cioffi et al, 2010;Úbeda-Manzanaro et al, 2010;Ferreira et al, 2011;Hashimoto et al, 2011;Cabral-deMello et al, 2012]. The U snDNA is a multigene family of non-coding RNAs that compounds the spliceosome machinery and may be subdivided into 5 types, including U1, U2, U4, U5, and U6 [Valadkhan, 2005].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, cases have been reported in which the two ribosomal genes are in the same locus (Cross et al, 2006;Fujiwara et al, 2007;Diniz et al, 2008). The U2 snRNA gene has been applied Within the fish group, only one work has reported the location of this probe, in four Batrachoididae species, and in that case the authors found three hybridization patterns: concentrated in one chromosome pair; dispersed through the genome; or both concentrated and dispersed (Úbeda-Manzanaro et al, 2010a). Recently, double-FISH studies with the same probes have been carried out in three species of Sparidae family (Merlo et al, in revision).…”
Section: Resultsmentioning
confidence: 99%
“…In some fish species, studies with (GATA)n repeats showed a dispersed localization throughout the chromosomes without any kind of preferential accumulation [Cross et al, 2006;Úbeda-Manzanaro et al, 2010;Traldi et al, 2013]. Although some (GATA)n clusters were detected in chromosomes of Parodontidae, especially in the sex chromosomes, an extensive number of dispersed copies in the karyotype is evident.…”
Section: Discussionmentioning
confidence: 99%